2007
DOI: 10.1111/j.1469-8749.2007.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental outcome in five children with Hurler syndrome after stem cell transplantation: a pilot study

Abstract: Hurler syndrome (mucopolysaccharidosis type 1H; MPS1H) is a lysosomal storage disease caused by a deficiency of α‐L‐iduronidase activity. The natural course of this neurodegenerative disease inevitably leads to premature death within the first 10 years of life. Enzyme replacement therapy is effective in correcting the enzymatic deficiency of organs other than the central nervous system. Hematopoietic stem cell transplantation (SCT) is the only treatment known to prevent psychomotor deterioration. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…This is in accordance with previously published data, where non-malignant disorders such as metabolic diseases and non-malignant hematological disorders were found to have an increased risk of graft failure. 38,39 Apart from killing of remnant malignant cells, the purpose of the conditioning regimen is mainly to suppress the recipient's immune system and prevent an immunological rejection of the infused donor hematopoietic cells. RIC regimens are; however, used in the elderly as well as in patients with comorbidities, who would probably not be able to tolerate the toxicity associated with myeloablative conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previously published data, where non-malignant disorders such as metabolic diseases and non-malignant hematological disorders were found to have an increased risk of graft failure. 38,39 Apart from killing of remnant malignant cells, the purpose of the conditioning regimen is mainly to suppress the recipient's immune system and prevent an immunological rejection of the infused donor hematopoietic cells. RIC regimens are; however, used in the elderly as well as in patients with comorbidities, who would probably not be able to tolerate the toxicity associated with myeloablative conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to HSCT, there have been studies showing a significant improvement of brain MR imaging features with regression of lesions and WMA following successful engraftment. 13,18,42 Those alterations were also accompanied by favorable neurologic outcome. 36 In addition, although it is widely accepted that HSCT has limited or no effect on skeletal manifestations of the disease, current research has shown that odontoid dysplasia can be normalized with the use of this treatment technique.…”
Section: Effect Of Therapeutic Regimens In Mr Imaging Findingsmentioning
confidence: 94%
“…18 In relation to their localization, cystic lesions tend to be linear, varying from patchy to diffuse, 12 and affect most brain parts, with periventricular white matter being the most common, followed by the corpus callosum (Fig 5), basal ganglia, subcortical white matter, thalami (Fig 4), and brain stem. 11,12,15,18,20,27,28,37,38,42 In most, dilated PVS range from 2 to 8 mm in diameter, 12,32 though giant cavitary lesions of 1.5 cm in the brain MR imaging of 1 patient with Hurler-Scheie syndrome were also described in the literature. 17 The cystic areas on MR imaging most likely correspond to perivascular expanded fluid spaces, first described as a neuropathologic autopsy sign by Dekaban and Constantopoulos.…”
Section: Brain Lesions and Enlarged Pvsmentioning
confidence: 99%
“…Dusing et al demonstraram deficiência nas habilidades motoras globais e finas em crianças com MPS tipo 1, usando a Escala de Bayley (4) e a Escala de Desenvolvimento de Peabody (5) . Em ambos os estudos, mesmo apresentando baixos níveis nessas habilidades, as crianças com MPS tipo 1 mostraram evolução após a intervenção clínica (13) , o que corrobora os achados do caso clínico aqui relatado. A melhora observada na motricidade global pode estar associada ao aprendizado obtido durante a intervenção fisioterapêutica, a qual estimulou o conhecimento de novos movimentos e posturas, permitindo à criança vivenciar e experimentar novos estímulos sensoriais, proprioceptivos, vestibulares e cognitivos.…”
Section: Discussionunclassified